Rethinking progressive and conservative values: Spain's new economy workers and their values. (1st January 2007) - ,
Abstract : Drawing on interviews carried out with workers in the new economy in Madrid, this paper argues that the dichotomy 'individualism versus collectivism' is inadequate to describe their value systems. It proposes instead an alternative typology based on distinctions between 'personal' and 'organic' values and 'diversified' and 'non-diversified' interests. The development of these values is placed in the context of the specific history of industralisation in southern Europe, which, along with eastern Europe, differs significantly from that of the economies of northern Europe which industrialised earlier and whose working classes developed different models of solidarity.